2017
DOI: 10.1038/srep39993
|View full text |Cite
|
Sign up to set email alerts
|

Observation and quantification of the quantum dynamics of a strong-field excited multi-level system

Abstract: The quantum dynamics of a V-type three-level system, whose two resonances are first excited by a weak probe pulse and subsequently modified by another strong one, is studied. The quantum dynamics of the multi-level system is closely related to the absorption spectrum of the transmitted probe pulse and its modification manifests itself as a modulation of the absorption line shape. Applying the dipole-control model, the modulation induced by the second strong pulse to the system’s dynamics is quantified by eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…For the noncollinear geometry depicted in Fig. 2, fast oscillations of the measured transient-absorption spectrum as a function of time delay τ cannot be distinguished and are averaged out [26,27]. Here, this is taken into account by convolving S 1 (ω, τ ) with a normalized Gaussian function G(τ, ∆τ ) of width ∆τ = 5 × 2π/ω L , which leads to…”
Section: A Three-level Model and Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the noncollinear geometry depicted in Fig. 2, fast oscillations of the measured transient-absorption spectrum as a function of time delay τ cannot be distinguished and are averaged out [26,27]. Here, this is taken into account by convolving S 1 (ω, τ ) with a normalized Gaussian function G(τ, ∆τ ) of width ∆τ = 5 × 2π/ω L , which leads to…”
Section: A Three-level Model and Equations Of Motionmentioning
confidence: 99%
“…The attention is thus focused on the characterization of the action of the pump pulse as a function of its parameters such as, e.g., intensity and laser frequency, and the main line-shape modifications are exclusively attributed to its nonlinear interaction with the system. Recent investigations of transient-absorption spectra in Rb atoms were based on this assumption [26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that the phase of a sample's polarization induced by a resonant laser field in an atomic system can be modified by a strong nonresonant laser field owing to the AC Stark effect [17][18][19][20]. This model is known as the dipole phase control theory and has been extended to multilevel and complex molecular systems by using medium-strength pump and weak probe pulses with the same frequency [21][22][23]. Actually, both the phase and amplitude of a sample's response in the time domain will be significantly modified by the AC stark effect and Rabi oscillation, respectively, regardless of whether the probe pulse precedes or follows the pump pulse.…”
Section: Introductionmentioning
confidence: 99%
“…If the duration of the probe pulse is comparable with that of the pump pulse, the absorption spectra do not provide the resolution necessary to access the real-time dynamics taking place during the pump pulse. This is for example the case when optical transitions have to be studied or controlled with optical femtosecond pump and probe pulses of equal duration [21][22][23][24]. The Rabi oscillations responsible for the appearance of LISs take place only within the pump pulse, and a probe pulse of equal duration does not have the required resolution to distinguish them.…”
Section: Introductionmentioning
confidence: 99%